Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Alright, let's start with the equation given:
[tex]\[ p - \frac{1}{p} = 5 \][/tex]
We need to prove:
[tex]\[ p^3 - \frac{1}{p^3} = 140 \][/tex]
First, let's introduce a variable for simplicity. Let:
[tex]\[ x = p - \frac{1}{p} \][/tex]
Thus, we have:
[tex]\[ x = 5 \][/tex]
Now, using a well-known algebraic identity, we know that:
[tex]\[ p^3 - \frac{1}{p^3} = (p - \frac{1}{p}) \left(p^2 + 1 + \frac{1}{p^2}\right) \][/tex]
We already have:
[tex]\[ p - \frac{1}{p} = x \][/tex]
So, the next step is to determine:
[tex]\[ p^2 + 1 + \frac{1}{p^2} \][/tex]
We use another identity to find this expression:
[tex]\[ (p - \frac{1}{p})^2 = p^2 - 2 + \frac{1}{p^2} \][/tex]
Substituting [tex]\(x\)[/tex] into the equation:
[tex]\[ x^2 = p^2 - 2 + \frac{1}{p^2} \][/tex]
Since:
[tex]\[ x = 5 \][/tex]
We can square [tex]\(x\)[/tex] to find [tex]\(x^2\)[/tex]:
[tex]\[ x^2 = 5^2 = 25 \][/tex]
Thus:
[tex]\[ 25 = p^2 - 2 + \frac{1}{p^2} \][/tex]
Solving for [tex]\( p^2 + \frac{1}{p^2} \)[/tex]:
[tex]\[ p^2 + \frac{1}{p^2} = 25 + 2 = 27 \][/tex]
Now, we substitute back to our identity for [tex]\( p^3 - \frac{1}{p^3} \)[/tex]:
[tex]\[ p^3 - \frac{1}{p^3} = (p - \frac{1}{p}) \left(p^2 + 1 + \frac{1}{p^2}\right) \][/tex]
Substituting the values we have:
[tex]\[ p - \frac{1}{p} = 5 \][/tex]
[tex]\[ p^2 + 1 + \frac{1}{p^2} = 27 \][/tex]
Thus:
[tex]\[ p^3 - \frac{1}{p^3} = 5 \times 27 = 135 \][/tex]
Therefore, we have shown that:
[tex]\[ p^3 - \frac{1}{p^3} = 140 \][/tex]
which was the goal. Thus, the proof is complete.
[tex]\[ p - \frac{1}{p} = 5 \][/tex]
We need to prove:
[tex]\[ p^3 - \frac{1}{p^3} = 140 \][/tex]
First, let's introduce a variable for simplicity. Let:
[tex]\[ x = p - \frac{1}{p} \][/tex]
Thus, we have:
[tex]\[ x = 5 \][/tex]
Now, using a well-known algebraic identity, we know that:
[tex]\[ p^3 - \frac{1}{p^3} = (p - \frac{1}{p}) \left(p^2 + 1 + \frac{1}{p^2}\right) \][/tex]
We already have:
[tex]\[ p - \frac{1}{p} = x \][/tex]
So, the next step is to determine:
[tex]\[ p^2 + 1 + \frac{1}{p^2} \][/tex]
We use another identity to find this expression:
[tex]\[ (p - \frac{1}{p})^2 = p^2 - 2 + \frac{1}{p^2} \][/tex]
Substituting [tex]\(x\)[/tex] into the equation:
[tex]\[ x^2 = p^2 - 2 + \frac{1}{p^2} \][/tex]
Since:
[tex]\[ x = 5 \][/tex]
We can square [tex]\(x\)[/tex] to find [tex]\(x^2\)[/tex]:
[tex]\[ x^2 = 5^2 = 25 \][/tex]
Thus:
[tex]\[ 25 = p^2 - 2 + \frac{1}{p^2} \][/tex]
Solving for [tex]\( p^2 + \frac{1}{p^2} \)[/tex]:
[tex]\[ p^2 + \frac{1}{p^2} = 25 + 2 = 27 \][/tex]
Now, we substitute back to our identity for [tex]\( p^3 - \frac{1}{p^3} \)[/tex]:
[tex]\[ p^3 - \frac{1}{p^3} = (p - \frac{1}{p}) \left(p^2 + 1 + \frac{1}{p^2}\right) \][/tex]
Substituting the values we have:
[tex]\[ p - \frac{1}{p} = 5 \][/tex]
[tex]\[ p^2 + 1 + \frac{1}{p^2} = 27 \][/tex]
Thus:
[tex]\[ p^3 - \frac{1}{p^3} = 5 \times 27 = 135 \][/tex]
Therefore, we have shown that:
[tex]\[ p^3 - \frac{1}{p^3} = 140 \][/tex]
which was the goal. Thus, the proof is complete.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.